RF-based plasma density diagnostic for investigation of wakefield of the beam in plasma of neutralizer - Urazbaev, A.B.R.; Ni, P. (Nazarbayev University, 2013)
The long-term goal of this project is to construct a mirror laboratory of ICF at our research center; therefore, we need highly qualified researchers who can use the accelerator effectively. This is a startup project aimed to enhance research capacity of Nazarbayev University (NU). It is planned to train the NU staff on the Neutralized Drift Compression Experiments-II accelerator (NDCX-II) at Berkeley.
Keywords: first research week; inertial confinement fusion; innovative scientific research; Neutralized Drift Compression Experiments-II accelerator